Analisis Tata Kelola Penanggulangan Bencana Banjir di Kelurahan Oesapa, Kecamatan Kelapa Lima, Kota Kupang - Indrika Amanda Junita Panggur; Amelia Irnawati Nendong; Delma Dassi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Flooding is one of the most frequent hydrometeorological disasters occurring in Kupang City and has significant social, economic, and environmental impacts. Oesapa Village, located in Kelapa Lima District, is one of the coastal areas with a relatively high level of vulnerability to flooding due to high rainfall intensity, rapid residential development, and the suboptimal condition of the drainage system. This study aims to analyze flood disaster management governance in Oesapa Village, Kelapa Lima District, Kupang City. The research employs a qualitative approach using a library research method. Data were collected from various secondary sources, including scientific journals, policy documents, disaster reports, laws and regulations, and other relevant official publications. Data analysis was conducted using content analysis through the stages of data reduction, data presentation, and conclusion drawing.The findings indicate that the Government of Kupang City has implemented various flood mitigation programs, including drainage construction, water channel normalization, disaster mitigation socialization, and institutional capacity strengthening. However, flooding continues to occur due to infrastructure limitations, low public awareness regarding environmental management, and suboptimal coordination among stakeholders. Analysis based on the Collaborative Governance perspective reveals that the success of flood disaster management is highly influenced by collaboration among government institutions, local communities, and other relevant actors. Therefore, strengthening a more integrated, participatory, and sustainable disaster governance system is necessary to enhance the effectiveness of flood disaster management in Oesapa Village.